PENERAPAN PRINSIP PRUDENTIAL BANKING PADA PEMBIAYAAN KREDIT USAHA RAKYAT MIKRO: STUDI PADA BANK SYARIAH INDONESIA CABANG BANDA ACEH - Azkal Azkia; Safira Mustaqilla (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
Kredit Usaha Rakyat (KUR) is a credit facility to middle to lower class customers that issued by banking industries in Indonesia, which focusses on aspects of livestock, trade, and agriculture. PT Bank Syariah Indonesia, Banda Aceh is one of bank company which issues this product and always applies prudent banking principles, especially in financing. The application of the prudential principle is carried out starting from the beginning of the debtor applying for credit analysis of KUR financing until the financing is paid off. This type of research is a qualitative descriptive approach through case studies. The result finds that the application of prudential banking principles applied to the company can be seen from the various provisions set by Bank Indonesia. The provisions of the prudential principle are the Capital Adequacy Ratio (CAR), namely the maximum credit provision (Maximum Lending Limit), the allowance for productive asset liabilities, and the provisions that regulate banking itself. The company can be seen from non-performing loans, it seems that their non-performing loans originated from year to year are increasing even though they have implemented the prudential principle, but there are still non-performing loans.